Macroeconomic Stability of The European Union Member States in The Light of The Macroeconomic Imbalance Procedure - Bogdan WLODARCZYK; Aleksandra OSTROWSKA (Communications of International Proceedings, 2020)
Macroeconomic stability, which is represented by an appropriate combination and levels of macroeconomic indicators, lays the foundations for attaining sustainable economic development over a long time horizon. Maintaining macroeconomic stability is particularly important in the EU countries, which compose a heterogenous structure in terms of both national economies and the development of financial markets. The EU member states are at different stages of their integration with the union. Most (19) are in the eurozone, having adopted the common currency, thereby abandoning autonomous monetary policy and transferring it to the European Central Bank. Critics of the common currency point to the risk of integrated monetary policy implementing the tools that might not be adequate for sustaining the stability of all national economies. Surveillance of the current economic situation is therefore crucial for the economic growth of these countries. The research subject raised in this paper is important for the present and future situation of the countries in the euro area and ones considering the date of access thereof. Monitoring macroeconomic stability is also significant in view of the current global situation, including the struggle with the COVID-19 pandemic. The purpose of this study has been to evaluate the macroeconomic stability of the EU countries based on data published under the framework of the Macroeconomic Imbalance Procedure (MIP) in 2011-2018. The research results suggested an overall improvement in the macroeconomic stability of the countries submitted to the analysis, which was implicated by the decreasing number of cases when the thresholds set for particular indicators were exceeded. Moreover, regardless of whether given countries belong to the eurozone or not, most cases of exceeding the thresholds were observed in the areas of public and private sector debt and in the international investment position as well as export market share. These findings point to the areas that require improvement in the analyzed countries.
Keywords: macroeconomic stability; European Union countries; Macroeconomic Imbalance Procedure